Delayed Fiscal Adjustment and Economic Growth: Empirical Evidence using Autoregressive Distributed Lag Bound Testing Model - Kanoun, Salem (International Journal of Economics and Financial Issues, 2019)
This study is an attempt to quantify the delayed fiscal adjustment using an accounting framework and to test its short and long run effects on growth in Tunisia by using Autoregressive Distributed Lag (ARDL) model over the period 1975-2015. We find that delayed fiscal adjustment hurts per capita GDP growth not only in the short run but also in the long run, which raises arguable evidence that the implementation of IMF supported programs is truly necessary in Tunisia in time of crisis particularly when public finance regulatory forces and the ability to adjust fail and become non-functional. This implies that any delay in bringing forward fiscal reforms is counterproductive in the short run and will result in net losses in per capita GDP growth in the long run. Keywords: Fiscal Sustainability, Delayed fiscal Adjustment, Economic Growth, ARDL JEL Classifications: E61 E62 DOI: https://doi.org/10.32479/ijefi.8026